Problem based learning Berbantuan Quizizz Terhadap Kemampuan Representasi Matematis dan Self-confidence Peserta Didik - Aminah, Rosyidatul; Sulistyoningsih, Titien; Prihaswati, Martyana (Journal of Lesson Study in Teacher Education, 2025)
This research is motivated by the results of the pre-cycle in class XI-2 of SMA Negeri 11 Semarang which showed that mathematical representation ability was relatively low with average mathematical representation ability test score of 45 with classical completion percentage of 19% and self-confidence level in moderate category of 49.75%. The purpose of this study was to describe the implementation of PBL assisted by quizizz to improve mathematical representation ability and self-confidence of class XI-2 students of SMA Negeri 11 Semarang in the 2024/2025 academic year. This research is classroom action research with three-cycle design that includes the planning, action implementation, observation, and reflection stages. The indicator of the success of this research is percentage of classical completion of mathematical representation ability test results is 80% reaching KKM 70 and average self-confidence is at least at 75% or very high. The results of this study are the percentage of pre-cycle completion is 19% increasing in cycle I to 55.6%, in cycle II to 69.4%, and in cycle III to 80.6%. While the percentage of pre-cycle self-confidence questionnaire data is 49.7%, in cycle I to 69.14%, in cycle II to 73.53%, and finally reaching 78.08% in cycle III with very high self-confidence category. It can be concluded that implementation of PBL assisted by quizizz can improve the mathematical representation ability and self-confidence of class XI-2 students of SMA Negeri 11 Semarang.